Karakteristik dan Efektivitas Formula Sabun Cuci Tangan Cair Handmade dalam Menurunkan Angka Kuman - Sriwulan Sriwulan; Susanti Dhini Anggraini; Nia Nurfitria; Kuntum Febriyantiningrum (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This study aims to compare the characteristics of the handmade liquid hand soap formula and its effectiveness in reducing the number of germs. The formulation used is the difference in the amount of EDTA, Texapon, and NaCl used in soap making. The characterization carried out was organoleptic, physical stability at room temperature, pH, viscosity, foam height and stability, water holding capacity, and density. Meanwhile, reduced number of germs was carried out by calculating the total plate number (ALT) of bacteria on the test taker hand before and after washing their hands. The results obtained were that the first formula (P1) which used less amounts of EDTA, Texapon, and NaCl had a bright color, lack of foam, perfect solubility,stable at room temperature, and did not cause a burning feeling in the hands. Whereas the second formulation (P2) with a higher amount of EDTA, Texapon, and NaCl hadexellence in the amoont of foam compared to the previous formula but the solubility was not perfect, less stable at room temperature and caused a burning feeling in the hands. The result of Pairef t test show that the t count is bigger than t table, so the different formulation had an effect on reducing the germ on the test taker hand based on ALT germ number parameter. P1 formulation can reduce the number of bacteria on hands by 47.64% and P2 formulation by 36.12%.